Theology in Ecological Perspective: An Interdisciplinary, Inquiry-Based Experiment - Butkus, Russell A. (Teaching theology and religion, 2008)
As the result of an extensive self-study for the purpose of reaccreditation, the Department of Theology at The University of Portland began offering a new series of courses called Theological Perspective Courses (THEP). THEP courses are upper division and offered by theology faculty in conjunction with another department that has required core courses in the College of Arts and Sciences. They are intended to be interdisciplinary, with two faculty members from different disciplines collaborating on new course design and implementation. THEP 482, Theology in Ecological Perspective, was one of the first two THEP courses taught. This article describes and reflects on the nature of this religion and science course in terms of subject matter, learning theory, and development of community. Several additional appendices to this article appear online at: http://www.wabashcenter.wabash.edu/journal/article2.aspx?id=12397